Report on police watchhouses in Queensland - Queensland. Criminal Justice Commission; Clair, F. J. (Frank J.) (Brisbane : The Commission, 1996)
Presents the findings and recommendations of the Criminal Justice Commission's research project on police watchhouses; linked issues of overcrowding, lengthy stays by prisoners and poor conditions for both police and prisoners in watchhouses in Queensland; public policy implications of not moving prisoners to the prison system; provision of health and medical services.
Chair: F.J. Clair.
"August 1996".
Includes bibliographical references (p. 99-100)
Keywords: Queensland Police Service; Arrest -- Queensland; Detention of persons -- Queensland; Police stations -- Queensland; Health services; Law enforcement - Prisons; Law enforcement - Custody; Law enforcement - Criminal law and procedure - Pretrial procedures; Government policy - State and territory - Queensland; Law enforcement - Police; Queensland (Qld)